2022
DOI: 10.1097/pec.0000000000002788
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Urgent Care Providers' Approach to Antibiotic Stewardship

Abstract: Background: Outpatient antibiotic prescribing for acute respiratory conditions is highest in urgent care settings; however, this has not been studied among pediatric urgent cares. The objective of this study was to evaluate pediatric urgent care providers' perceptions of antibiotic stewardship.Methods: Members of the Society for Pediatric Urgent Care were recruited via email to participate in a quality improvement antibiotic stewardship project. A preimplementation survey was sent to participants via email in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Clinicians working in the ED often perceive a demand for antibiotics from the caregiver [ 20 ]. Yet, studies examining the drivers behind ED attendance commonly reveal that caregivers primarily seek explanations for their child’s fever, reassurance, and guidance on symptom management [ 21 , 22 , 23 ].…”
Section: Factors Affecting Antibiotic Prescribing In Pemmentioning
confidence: 99%
“…Clinicians working in the ED often perceive a demand for antibiotics from the caregiver [ 20 ]. Yet, studies examining the drivers behind ED attendance commonly reveal that caregivers primarily seek explanations for their child’s fever, reassurance, and guidance on symptom management [ 21 , 22 , 23 ].…”
Section: Factors Affecting Antibiotic Prescribing In Pemmentioning
confidence: 99%
“…In a national survey of pediatric UC providers, 93% of clinicians reported family expectations as a barrier to following antibiotic stewardship guidelines 4 . However, Mangione-Smith et al 5 demonstrated that providers are not good predictors of family expectations.…”
mentioning
confidence: 99%